Modified silicon monoxide battery negative electrode composite material and preparation method and application thereof
The porous silicon oxide surface is formed by electron beam irradiation and carbonized. Combined with the preparation of modified binder, the structural instability problem caused by volume changes in the negative electrode material of lithium-ion battery is solved, and higher mechanical stability and conductivity are achieved.
Patent Information
- Application Number
- CN202510173602.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-18
AI Technical Summary
The stress caused by volume changes in the existing lithium-ion battery negative electrode materials cannot be effectively relieved during the charge and discharge cycle, resulting in unstable structure and insufficient adhesive strength and easy to fall off.
By electron beam irradiating the silicon oxide powder, a porous structure is formed, and a covalent encapsulation layer is formed on the surface and then carbonized to form a dense carbonized layer. At the same time, pyrene groups are introduced into the acrylic monomer and modified with stearic acid, a modified binder is prepared to improve the mechanical stability of the material.
Effectively alleviate the stress caused by volume changes, maintain structural integrity, improve the strength and stability of the adhesive, avoid damage and fall off, and enhance conductivity and rate performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery preparation, and specifically relates to a modified silicon oxide battery negative electrode composite material and a preparation method and application thereof. Background Art
[0002] Silicon negative electrode materials have extremely high theoretical capacity. This outstanding characteristic gives silicon negative electrodes higher energy storage capacity, which can effectively improve the battery's range or the overall energy density of the energy storage system. It is worth noting that the electrons inside the silicon crystal are tightly fixed around the atoms due to the strong binding effect of covalent bonds and are difficult to move freely, which leads to the relatively poor conductivity of the silicon material itself. In addition, the process of lithium embedding into silicon involves an alloying reaction, which is accompanied by significant volume changes during the battery's charge and discharge cycle.
[0003] Chinese patent application CN112678807B discloses a modified silicon dioxide / carbon nanotube composite negative electrode material and a preparation method thereof, wherein a silane coupling agent is used to chemically react with silicon-based material particles and polymerize on the surface to form a special three-dimensional structure with carbon nanotube granulation. However, the silane coupling agent has a low degree of polymerization, a short molecular chain, and weak intermolecular interaction, and cannot effectively alleviate the volume expansion of the negative electrode material.
[0004] Chinese patent application CN116632234A discloses a binder for negative electrode materials of lithium batteries and a preparation method thereof. The binder prepared by butadiene compounds, styrene compounds and polyacrylonitrile has excellent wetting effect on negative electrode materials and can achieve good bonding effect with negative electrode materials. In addition, propylene sulfite is used as a film-forming additive, which has good compatibility with the matrix emulsion and forms a uniform and stable system. However, when the negative electrode material expands, the binder is not strong enough and is easy to fall off. Summary of the invention
[0005] The purpose of the present invention is to provide a modified silicon oxide battery negative electrode composite material, which forms ablated silicon oxide powder with a rough surface and a porous structure with a large specific surface area by electron beam irradiation of silicon oxide powder, uniformly loads lithium ions on the surface, and forms a dense carbonized layer after carbonization of a covalent coating layer generated in situ on the surface. The carbonized layer has good strength and can effectively relieve the stress caused by volume change. The pyrene group is introduced into an acrylic acid monomer and modified with stearic acid to give the binder a certain rigidity. The binder still has excellent mechanical stability while suppressing the volume expansion of silicon oxide, thereby avoiding damage and shedding of the binder.
[0006] The purpose of the present invention can be achieved by the following technical solutions: A modified silicon oxide battery negative electrode composite material is prepared by the following steps: Step 1: Place silicon oxide powder with a particle size of 100-120 nm in a stainless steel shell (outer diameter 28-30 mm, height 3-4 mm, shell thickness 0.3-0.32 mm), place the shell in the center of the mold, and press the silicon oxide powder into the shell using a pressure of 5-6 MPa on a tablet press; place the shell containing silicon oxide powder on the electron beam workbench, start the equipment and turn on the vacuum system. When the vacuum degree of the vacuum chamber reaches 6.5×10 -3 Pa, the acceleration voltage is 25-28KV, the pulse duration is 2-4μs, and the irradiation energy is 2.2-2.5J / cm 2 The electron beam is directly irradiated on the silicon oxide powder to obtain the ablated silicon oxide powder.
[0007] Step 2: Add the ablated silicon oxide powder and a sodium hydroxide solution with a mass fraction of 5-7% into a reactor, stir for 40-60 minutes at 80-90°C and 500-600r / min, cool naturally, filter, wash the filter cake with deionized water until the last washing liquid is neutral, and vacuum dry at 60-80°C for 1-2h to obtain modified silicon oxide powder; add ethyl p-aminobenzoate and modified silicon oxide powder into a reactor, stir for 1-2h at 50-60°C and 500-600r / min, add lithium sulfate and deionized water into the reactor, continue stirring for 1-2h, filter, wash the filter cake with anhydrous ethanol 2-3 times, and vacuum dry at 60-80°C for 1-2h to obtain composite silicon oxide powder.
[0008] Step 3: Add composite silicon oxide powder, 2,5-diaminobenzoic acid and deionized water into a reactor, stir at 50-60°C and 500-700r / min for 40-45min, add tetrakis(4-formylphenyl)ethylene into the reactor, stir at 20-25°C and 500-600r / min for 10-12min, add dimethylacetamide, N,N-dimethylformamide and 4mol / L acetic acid solution into the reactor, continue to react for 1-2h, filter, wash the filter cake with deionized water 2-3 times, and vacuum dry at 60-80°C for 1-2h to obtain a precursor powder; place the precursor powder in a muffle furnace, keep it warm at 950-1000°C for 2-3h under nitrogen protection to carbonize the organic matter in the precursor powder, cool it naturally, and obtain a modified silicon oxide negative electrode substrate material.
[0009] Step 4: Add 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, sodium borohydride and deionized water into a reactor, stir for 40-60 min at 70-80°C and 500-600 r / min, filter, wash the filter cake with tetrahydrofuran 2-3 times to obtain a reduced product; add the reduced product, an acrylic acid solution with a neutralization degree of 65-70% and deionized water into a reactor, stir for 40-60 min at 70-80°C and 500-600 r / min, then add stearic acid into the reactor, and heat at 50-60°C and 500-600 r / m in conditions of stirring for 1-2 hours, cooling to 55-65°C, adding sodium sulfite as an initiator, acrylic acid solution with a neutralization degree of 65-70% and hydroxymethyl acrylamide as a cross-linking agent into the reactor, introducing nitrogen protection, heating to 70-80°C, stirring at 500-600r / min for 3-4 hours, filtering, washing the filter cake with anhydrous ethanol for 2-3 times, and vacuum drying at 60-80°C for 1-2 hours to obtain a modified binder; the modified silicon oxide negative electrode base material and the modified binder are evenly mixed in a mass ratio of 8:1 to obtain a modified silicon oxide battery negative electrode composite material.
[0010] Furthermore, in step 2, the ratio of the ablated silicon oxide powder to the sodium hydroxide solution is 10-12 g: 500-600 mL.
[0011] Furthermore, in step 2, the dosage ratio of ethyl p-aminobenzoate, modified silicon oxide powder, lithium sulfate and deionized water is 200-300 mL: 5-6 g: 3-4 g: 400-500 mL.
[0012] Furthermore, in step three, the dosage ratio of composite silicon oxide powder, 2,5-diaminobenzoic acid, deionized water, tetrakis(4-formylphenyl)ethylene, dimethylacetamide, N,N-dimethylformamide, and acetic acid solution is 4-5g:8-9g:400-500mL:8-9g:10-12mL:10-12mL:5-6mL.
[0013] Furthermore, in step 4, the usage ratio of 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, sodium borohydride and deionized water is 7-9 g: 30-40 g: 300-400 mL.
[0014] Furthermore, in step 4, the dosage ratio of the reducing product, acrylic acid solution, deionized water, stearic acid, sodium sulfite and hydroxymethyl acrylamide is 5-6g:80-90mL:200-300mL:20-30g:80-100mL:80-100mL.
[0015] The present invention also provides an application of the modified silicon oxide battery negative electrode composite material to prepare a lithium battery negative electrode.
[0016] Beneficial effects of the present invention: 1. The modified silicon oxide battery negative electrode composite material of the present invention is prepared by modifying the silicon oxide negative electrode base material and the modified binder. In the application of the negative electrode of the lithium battery, it can effectively alleviate the stress caused by the volume change and maintain the structural integrity of the silicon oxide negative electrode material during the charging and discharging process; the carbonized layer wraps the lithium element inside, effectively reduces the occurrence of side reactions, and stabilizes the SEI layer (solid electrolyte interface layer); the modified binder has good adhesion and strength, which can prevent the negative electrode material from being damaged and falling off.
[0017] 2. The modified silicon oxide negative electrode substrate material of the present invention forms ablated silicon oxide powder with a rough surface and a porous structure with a large specific surface area by electron beam irradiating silicon oxide powder, which is beneficial to the diffusion of lithium ions and the transmission of electrons, and the rough porous structure can effectively alleviate volume expansion; lithium atoms are loaded on the surface of the ablated silicon oxide powder by using ethyl para-aminobenzoate as a bridge, and then a covalent coating layer with a certain strength is generated in situ on its surface. After high-temperature carbonization, a dense carbonized layer is formed, which is beneficial to better avoid the volume expansion effect, and the lithium element is wrapped inside, effectively reducing the contact with the electrolyte, thereby reducing the occurrence of side reactions, stabilizing the SEI layer, avoiding excessive consumption of lithium ions, and improving the coulombic efficiency of the first cycle.
[0018] 3. The modified binder of the present invention is generated by introducing pyrene groups into acrylic monomers for polymerization and modifying them with stearic acid. The pyrene groups are rigid groups that give the binder a certain rigidity. The binder still has excellent mechanical stability when suppressing the volume expansion of silicon dioxide and can improve the transmission of carriers, which helps to improve the overall electronic conductivity of the negative electrode material and improve the rate performance of the battery. The mobility of the polymer chain segments is increased through the modification of stearic acid, which helps to avoid the problem of decreased flexibility of the binder caused by the introduction of rigid groups, thereby avoiding damage and shedding of the binder. The dense carbonized layer has a certain pore structure, which provides a channel for penetration and diffusion of the binder. When the binder contacts the surface of the carbonized layer, it can penetrate into the pores and form a closer contact with the carbonized layer, which helps to improve the bonding strength and further prevent damage and shedding. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Example 1: A modified silicon oxide battery negative electrode composite material is prepared by the following steps: S1: Place silicon dioxide powder with a particle size of 100-120 nm in a stainless steel shell (outer diameter 28 mm, height 3 mm, shell thickness 0.3 mm), place the shell in the center of the mold, and press the silicon dioxide powder into the shell using a pressure of 5 MPa on a tablet press; place the shell containing silicon dioxide powder on the electron beam workbench, start the equipment and turn on the vacuum system. When the vacuum degree of the vacuum chamber reaches 6.5×10 -3 Pa, the acceleration voltage is 25KV, the pulse duration is 2μs, and the irradiation energy is 2.2J / cm 2 The electron beam is directly irradiated on the silicon oxide powder to obtain the ablated silicon oxide powder.
[0021] Electron beam irradiation causes the surface temperature to rise above the melting point of silicon oxide, resulting in ablation of the silicon oxide structure, thereby forming a porous structure with a rough surface and a large specific surface area, which is beneficial to the diffusion of lithium ions and the transmission of electrons. During the charge and discharge process of lithium-ion batteries, the negative electrode material will expand and contract in volume. The porous structure of silicon oxide negative electrode material can buffer this volume change through its porosity, thereby maintaining the stability of the electrode structure.
[0022] S2: 10g of ablated silicon oxide powder and 500mL of 5% sodium hydroxide solution were added to a reactor, stirred at 80°C and 500r / min for 40min, cooled naturally, filtered, and the filter cake was washed with deionized water until the last washing liquid was neutral, and dried under vacuum at 60°C for 1h to obtain modified silicon oxide powder; 200mL of ethyl p-aminobenzoate and 5g of modified silicon oxide powder were added to a reactor, stirred at 50°C and 500r / min for 1h, 3g of lithium sulfate and 400mL of deionized water were added to the reactor, stirred for 1h, filtered, and the filter cake was washed twice with anhydrous ethanol, and dried under vacuum at 60°C for 1h to obtain composite silicon oxide powder.
[0023] After being treated with sodium hydroxide, hydroxyl groups are formed on the surface of the ablated silicon oxide powder and react with the amino group of ethyl p-aminobenzoate. Under the action of hydrolysis, carboxyl groups are exposed to react with lithium ions to evenly load the lithium ions on the surface of the ablated silicon oxide powder.
[0024] S3: 4 g of composite silicon oxide powder, 8 g of 2,5-diaminobenzoic acid and 400 mL of deionized water were added to the reactor, stirred at 50°C and 500 r / min for 40 min, 8 g of tetrakis(4-formylphenyl)ethylene was added to the reactor, stirred at 20°C and 500 r / min for 10 min, 10 mL of dimethylacetamide, 10 mL of N,N-dimethylformamide and 5 mL of 4 mol / L acetic acid solution were added to the reactor, the reaction was continued for 1 h, filtered, the filter cake was washed twice with deionized water, and vacuum dried at 60°C for 1 h to obtain a precursor powder; the precursor powder was placed in a muffle furnace, kept warm at 950°C under nitrogen protection for 2 h to carbonize the organic matter in the precursor powder, and naturally cooled to obtain a modified silicon oxide negative electrode substrate material.
[0025] The remaining hydroxyl groups on the surface of the composite silicon oxide powder are chemically bonded with the carboxyl groups of 2,5-diaminobenzoic acid, and then reacted with tetrakis(4-formylphenyl)ethylene to generate a covalent coating layer with a certain strength. After carbonization, a dense carbonized layer is formed on the surface of the silicon oxide powder. The carbonized layer wraps the lithium element inside, effectively reducing the contact with the electrolyte, thereby reducing the occurrence of side reactions, stabilizing the SEI layer (solid electrolyte interface layer), avoiding excessive consumption of lithium ions, and reducing the loss of irreversible capacity.
[0026] S4: 7 g of 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 30 g of sodium borohydride and 300 mL of deionized water were added to a reactor, stirred at 70°C and 500 r / min for 40 min, filtered, and the filter cake was washed twice with tetrahydrofuran to obtain a reduced product; 5 g of the reduced product, 80 mL of an acrylic acid solution with a neutralization degree of 65% and 200 mL of deionized water were added to a reactor, stirred at 70°C and 500 r / min for 40 min, and then 20 g of stearic acid was added to the reactor, stirred at 50°C and 500 r / min for 1 h, cooled to 55°C, 80 mL of sodium sulfite as an initiator, 80 mL of acrylic acid solution with a neutralization degree of 65% and 80 mL of hydroxymethyl acrylamide as a cross-linking agent were added to the reactor, nitrogen was introduced for protection, heated to 70°C, stirred at 500 r / min for 3 h, filtered, the filter cake was washed twice with anhydrous ethanol, and vacuum dried at 60°C for 1 h to obtain a modified binder.
[0027] The aldehyde group is reduced to a hydroxyl group by sodium borohydride, and the pyrene group is introduced into the acrylic monomer for polymerization, and then modified with stearic acid to obtain a modified binder. The pyrene group is a rigid group, which gives the binder a certain rigidity, ensuring that the modified binder still has excellent mechanical stability when suppressing the volume expansion of silicon oxide, and can improve the transmission of carriers, which helps to improve the overall electronic conductivity of the substrate material and improve the rate performance of the battery. The introduction of rigid groups usually leads to a decrease in the flexibility of the polymer chain segments. The steric hindrance of the rigid groups is large, making it difficult for the polymer chain segments to deform when subjected to external forces, thereby reducing the flexibility of the material. The mobility of the polymer chain segments is increased by grafting stearic acid, making the material more likely to deform when subjected to external forces, thereby improving the flexibility and helping to avoid damage and shedding of the substrate material.
[0028] S5: The modified silicon oxide negative electrode base material and the modified binder are mixed evenly in a mass ratio of 8:1 to obtain a modified silicon oxide battery negative electrode composite material.
[0029] Example 2: A modified silicon oxide battery negative electrode composite material is prepared by the following steps: S1: Place silicon dioxide powder with a particle size of 100-120 nm in a stainless steel shell (outer diameter 29 mm, height 3.5 mm, shell thickness 0.31 mm), place the shell in the center of the mold, and press the silicon dioxide powder into the shell using a pressure of 5 MPa on a tablet press; place the shell containing silicon dioxide powder on the electron beam workbench, start the equipment and turn on the vacuum system. When the vacuum degree of the vacuum chamber reaches 6.5×10 -3 Pa, the acceleration voltage is 27KV, the pulse duration is 3μs, and the irradiation energy is 2.3J / cm 2 The electron beam is directly irradiated on the silicon oxide powder to obtain the ablated silicon oxide powder.
[0030] S2: 11 g of ablated silicon oxide powder and 550 mL of 6% sodium hydroxide solution were added to a reactor, stirred at 85°C and 550 r / min for 50 min, cooled naturally, filtered, and the filter cake was washed with deionized water until the last washing liquid was neutral, and vacuum dried at 70°C for 1.5 h to obtain modified silicon oxide powder; 250 mL of ethyl p-aminobenzoate and 5.5 g of modified silicon oxide powder were added to a reactor, stirred at 55°C and 550 r / min for 1.5 h, 3.5 g of lithium sulfate and 450 mL of deionized water were added to the reactor, stirred for 1.5 h, filtered, and the filter cake was washed with anhydrous ethanol 3 times, and vacuum dried at 70°C for 1.5 h to obtain composite silicon oxide powder.
[0031] S3: 4.5g of composite silicon oxide powder, 8.5g of 2,5-diaminobenzoic acid and 450mL of deionized water were added to the reactor, stirred at 55°C and 600r / min for 43min, 8.5g of tetrakis(4-formylphenyl)ethylene was added to the reactor, stirred at 23°C and 550r / min for 11min, 11mL of dimethylacetamide, 11mL of N,N-dimethylformamide and 5.5mL of 4mol / L acetic acid solution were added to the reactor, the reaction was continued for 1.5h, filtered, the filter cake was washed with deionized water 3 times, and vacuum dried at 70°C for 1.5h to obtain a precursor powder; the precursor powder was placed in a muffle furnace, kept warm at 980°C under nitrogen protection for 2.5h to carbonize the organic matter in the precursor powder, and naturally cooled to obtain a modified silicon oxide negative electrode substrate material.
[0032] S4: 8 g of 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 35 g of sodium borohydride and 350 mL of deionized water were added to a reactor, stirred at 78°C and 550 r / min for 50 min, filtered, and the filter cake was washed with tetrahydrofuran three times to obtain a reduced product; 5.5 g of the reduced product, 85 mL of an acrylic acid solution with a neutralization degree of 68% and 250 mL of deionized water were added to a reactor, stirred at 78°C and 550 r / min for 50 min, and 250 mL of deionized water were added to a reactor. g stearic acid was added into the reactor, stirred at 55°C and 550r / min for 1.5h, cooled to 60°C, 90mL of sodium sulfite as an initiator, 85mL of acrylic acid solution with a neutralization degree of 68% and 90mL of hydroxymethyl acrylamide as a cross-linking agent were added into the reactor, nitrogen was introduced for protection, heated to 75°C, stirred at 550r / min for 3.5h, filtered, the filter cake was washed with anhydrous ethanol for 3 times, and vacuum dried at 70°C for 1.5h to obtain a modified binder.
[0033] S5: The modified silicon oxide negative electrode base material and the modified binder are mixed evenly in a mass ratio of 8:1 to obtain a modified silicon oxide battery negative electrode composite material.
[0034] Example 3: A modified silicon oxide battery negative electrode composite material is prepared by the following steps: S1: Place silicon dioxide powder with a particle size of 100-120 nm in a stainless steel shell (outer diameter 30 mm, height 4 mm, shell thickness 0.32 mm), place the shell in the center of the mold, and press the silicon dioxide powder into the shell using a pressure of 6 MPa on a tablet press; place the shell containing silicon dioxide powder on the electron beam workbench, start the equipment and turn on the vacuum system. When the vacuum degree of the vacuum chamber reaches 6.5×10 -3 Pa, the acceleration voltage is 28KV, the pulse duration is 4μs, and the irradiation energy is 2.5J / cm 2The electron beam is directly irradiated on the silicon oxide powder to obtain the ablated silicon oxide powder.
[0035] S2: 12 g of ablated silicon oxide powder and 600 mL of 7% sodium hydroxide solution were added to a reactor, stirred at 90°C and 600 r / min for 60 min, cooled naturally, filtered, and the filter cake was washed with deionized water until the last washing liquid was neutral, and vacuum dried at 80°C for 2 h to obtain modified silicon oxide powder; 300 mL of ethyl p-aminobenzoate and 6 g of modified silicon oxide powder were added to a reactor, stirred at 60°C and 600 r / min for 2 h, 4 g of lithium sulfate and 500 mL of deionized water were added to the reactor, stirred for 2 h, filtered, and the filter cake was washed with anhydrous ethanol 3 times, and vacuum dried at 80°C for 2 h to obtain composite silicon oxide powder.
[0036] S3: Add 5g of composite silicon oxide powder, 9g of 2,5-diaminobenzoic acid and 500mL of deionized water into the reactor, stir at 60°C and 700r / min for 45min, add 9g of tetrakis(4-formylphenyl)ethylene into the reactor, stir at 25°C and 600r / min for 12min, add 12mL of dimethylacetamide, 12mL of N,N-dimethylformamide and 6mL of 4mol / L acetic acid solution into the reactor, continue the reaction for 2h, filter, wash the filter cake with deionized water 3 times, and vacuum dry at 80°C for 2h to obtain a precursor powder; place the precursor powder in a muffle furnace, keep it warm at 1000°C for 3h under nitrogen protection to carbonize the organic matter in the precursor powder, cool it naturally, and obtain a modified silicon oxide negative electrode substrate material.
[0037] S4: 9 g of 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 40 g of sodium borohydride and 400 mL of deionized water were added to a reactor, stirred at 80°C and 600 r / min for 60 min, filtered, and the filter cake was washed with tetrahydrofuran three times to obtain a reduced product; 6 g of the reduced product, 90 mL of an acrylic acid solution with a neutralization degree of 70% and 300 mL of deionized water were added to a reactor, stirred at 80°C and 600 r / min for 60 min, and then 3 0g of stearic acid was added to the reactor, stirred at 60℃ and 600r / min for 2h, cooled to 65℃, 100mL of sodium sulfite as an initiator, 90mL of acrylic acid solution with a neutralization degree of 70% and 100mL of hydroxymethyl acrylamide as a cross-linking agent were added to the reactor, nitrogen was introduced for protection, heated to 80℃, stirred at 600r / min for 4h, filtered, the filter cake was washed with anhydrous ethanol for 3 times, and vacuum dried at 80℃ for 2h to obtain a modified binder.
[0038] S5: The modified silicon oxide negative electrode base material and the modified binder are mixed evenly in a mass ratio of 8:1 to obtain a modified silicon oxide battery negative electrode composite material.
[0039] Comparative Example 1: Based on Example 3, the ablated silicon oxide powder in step S2 is replaced by silicon oxide powder (particle size of 100-120 nm) in step S1, and the remaining steps remain unchanged to prepare a modified silicon oxide battery negative electrode composite material.
[0040] Comparative Example 2: Based on Example 3, ethyl p-aminobenzoate in step S2 is omitted, and the remaining steps remain unchanged to prepare a modified silicon oxide battery negative electrode composite material.
[0041] Comparative Example 3: Based on Example 3, 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene in step S4 is omitted, and the remaining steps remain unchanged to prepare a modified silicon oxide battery negative electrode composite material.
[0042] Comparative Example 4: Based on Example 3, the stearic acid in step S4 was omitted, and the other steps remained unchanged to prepare a modified silicon oxide battery negative electrode composite material.
[0043] In the embodiments and comparative examples: The electron beam device model is HOPE-I.
[0044] Silicon dioxide powder was purchased from Hengjing Crystal Rock New Energy Technology Co., Ltd.
[0045] Tetrakis(4-formylphenyl)ethylene was purchased from Guangzhou Jiatu Technology Co., Ltd.
[0046] 1,3,6,8-Tetrakis(4-formaldehydephenyl)-pyrene was purchased from Xi'an Qiyue Biotechnology Co., Ltd.
[0047] Ethyl p-aminobenzoate, lithium sulfate, 2,5-diaminobenzoic acid, dimethylacetamide, N,N-dimethylformamide, acetic acid, hydroxymethyl acrylamide, sodium sulfite, and sodium borohydride were purchased from Sigma-Aldrich.
[0048] The modified silicon oxide battery negative electrode composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were placed in a resistivity tester and the powder resistivity test was performed at a pressure of 20 MPa; The prepared negative electrode composite material was cut into a size of 15mm×20mm, and the negative electrode composite material was attached to the electrode surface on one side and to the steel plate on the other side using 3M pressure-sensitive adhesive (model VHB). The steel plate and the electrode were then fixed on a stretching fixture, and the negative electrode sheet to be tested was stretched at a certain speed for a 180-degree peeling test. When the conductive current collector was completely peeled off, the detected data was the peeling force (N / m).
[0049] The modified silicon oxide battery negative electrode composite material and conductive carbon black were added to 400 mL of deionized water in a mass ratio of 8:1, and the slurry was evenly dispersed using a homogenizer at a speed of 700 r / min. Then, the slurry was evenly coated on a copper foil using a push rod and dried in a vacuum oven at 120°C for 14 h to prepare a working electrode. A lithium sheet was used as a counter electrode, a glass fiber membrane (purchased from Whatman, UK) was used as a diaphragm, and 1 mol / L lithium tetrafluoroborate (the solvent was methoxyethane and ethylene carbonate in a volume ratio of 1:1) was used as an electrolyte. 1% of vinylene carbonate and 5% of fluoroethylene carbonate were added to the electrolyte, and button cells were assembled in an argon atmosphere in a Braun inert gas glove box in Germany.
[0050] An in-situ volume monitor (GVM2200) was used to monitor the volume change of the battery in real time during the charge and discharge process. The charge and discharge test of the button battery was carried out on the LAND battery test system of Wuhan Jinnuo Electronics Co., Ltd. The battery was subjected to constant current charge and discharge test. The measured voltage range was 0.005-2V, and the first cycle was 0.02C (1C=4200mAg -1 ) was activated at a low current density, and then a long cycle performance test was performed at a current density of 0.1C. The performance test results of the modified silicon oxide battery negative electrode composite material are shown in Table 1: Table 1 Performance test results of modified silicon oxide battery negative electrode composite materials
[0051] It can be seen from Table 1 that the percentage change in volume of the modified silicon oxide battery negative electrode composite materials obtained in Examples 1 to 3 of the present invention is significantly lower than that of the comparative example, and the initial efficiency, conductivity and peeling strength are significantly higher than those of the comparative example. In Comparative Example 1, the ablated silicon oxide powder is replaced with silicon oxide powder, resulting in the loss of surface roughness, large specific surface area and porosity, and the lithium ions cannot be more evenly distributed inside the material, thereby aggravating the local stress concentration caused by uneven lithium ion embedding, and cannot provide more active sites for the embedding and extraction of lithium ions, thereby reducing the initial efficiency. The loss of the porous structure cannot provide additional accommodation space for the volume expansion of silicon oxide, reducing the direct contact area with the electrolyte, resulting in fewer transmission channels for electrons and ions between the materials, thereby reducing the conductivity.
[0052] In Comparative Example 2, ethyl p-aminobenzoate is not added, resulting in the inability of lithium atoms to be stably and evenly loaded on the surface of silicon oxide, and unable to be better embedded and removed. As a result, during the first lithium insertion process, the lithium ion concentration is too high in some parts and insufficient in some parts. Side reactions are prone to occur in areas with high lithium ion concentrations, forming irreversible inert substances, thereby reducing the initial efficiency. If lithium atoms cannot be better embedded in and removed from silicon oxide, the diffusion path of lithium ions will be blocked, which will increase the internal resistance of the battery and reduce the conductivity.
[0053] In Comparative Example 3, 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene is not added, resulting in no pyrene group being introduced into the modified binder, which cannot improve the rigidity and strength of the modified binder and cannot help alleviate the volume change. In addition, the pyrene group can improve the transport of carriers, help improve the overall electronic conductivity of the negative electrode material, and improve the rate performance of the battery, thereby reducing the conductivity, resulting in an increase in the internal resistance of the battery, and the diffusion path of lithium ions is blocked, which in turn affects the initial efficiency. When suppressing the volume expansion of silicon oxide, the modified binder does not have sufficient strength to maintain stability, and is easily peeled off from the negative electrode material.
[0054] In Comparative Example 4, no stearic acid is added, which will cause the rigidity of the modified binder to be too high, resulting in a problem of reduced flexibility, thereby avoiding damage and falling off of the binder.
[0055] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0056] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a modified silicon oxide battery negative electrode composite material, characterized in that: The steps include: Step 1: Add ethyl p-aminobenzoate and modified silicon oxide powder into a reaction kettle, stir at 50-60°C and 500-600r / min for 1-2h, add lithium sulfate and deionized water into the reaction kettle, continue stirring for 1-2h, filter, wash the filter cake with anhydrous ethanol 2-3 times, and vacuum dry to obtain composite silicon oxide powder; Step 2: Add composite silicon oxide powder, 2,5-diaminobenzoic acid and deionized water into a reactor, stir at 50-60°C and 500-700r / min for 40-45min, add tetrakis(4-formylphenyl)ethylene into the reactor, stir at 20-25°C and 500-600r / min for 10-12min, add dimethylacetamide, N,N-dimethylformamide and 4mol / L acetic acid solution into the reactor, continue to react for 1-2h, filter, wash the filter cake with deionized water 2-3 times, and vacuum dry to obtain a precursor powder; place the precursor powder in a muffle furnace, keep warm at 950-1000°C for 2-3h under nitrogen protection, and cool naturally to obtain a modified silicon oxide negative electrode substrate material; Step 3: Evenly mix the modified silicon oxide negative electrode base material and the modified binder in a mass ratio of 8:1 to obtain a modified silicon oxide battery negative electrode composite material.
2. The method for preparing a modified silicon oxide battery negative electrode composite material according to claim 1, characterized in that: The modified silicon dioxide powder in step 1 is prepared by the following steps: Add the ablated silicon dioxide powder and 5-7wt% sodium hydroxide solution into the reactor in a dosage ratio of 10-12g:500-600mL, stir at 80-90°C and 500-600r / min for 40-60min, cool naturally, filter, wash the filter cake with deionized water until the last washing liquid is neutral, and vacuum dry to obtain modified silicon dioxide powder.
3. The method for preparing a modified silicon oxide battery negative electrode composite material according to claim 2, characterized in that: The ablated silicon oxide powder is prepared by the following steps: The silicon oxide powder with a particle size of 100-120 nm was placed in a stainless steel shell, and the shell was placed in the center of the mold. The silicon oxide powder was pressed into the shell using a pressure of 5-6 MPa on a tablet press, and the shell was placed on an electron beam workbench. The equipment was started and the vacuum system was turned on. When the vacuum degree of the vacuum chamber reached 6.5×10 -3 Pa, acceleration voltage 25-28KV, pulse duration 2-4μs, irradiation energy 2.2-2.5J / cm 2 When an electron beam is applied, the silicon oxide powder is directly irradiated to obtain ablated silicon oxide powder.
4. The method for preparing a modified silicon oxide battery negative electrode composite material according to claim 1, characterized in that: The dosage ratio of ethyl p-aminobenzoate, modified silicon oxide powder, lithium sulfate and deionized water in step 1 is 200-300 mL: 5-6 g: 3-4 g: 400-500 mL.
5. The method for preparing a modified silicon oxide battery negative electrode composite material according to claim 1, characterized in that: The dosage ratio of the composite silicon oxide powder, 2,5-diaminobenzoic acid, deionized water, tetrakis(4-formylphenyl)ethylene, dimethylacetamide, N,N-dimethylformamide, and acetic acid solution in step 2 is 4-5g:8-9g:400-500mL:8-9g:10-12mL:10-12mL:5-6mL.
6. The method for preparing a modified silicon oxide battery negative electrode composite material according to claim 1, characterized in that: The modified binder in step 3 is prepared by the following steps: The reducing product, 1 / 2 of the total amount of acrylic acid solution with a neutralization degree of 65-70% and deionized water are added to a reactor, stirred at 70-80°C and 500-600r / min for 40-60min, then stearic acid is added to the reactor, stirred at 50-60°C and 500-600r / min for 1-2h, cooled to 55-65°C, sodium sulfite, the remaining acrylic acid solution with a neutralization degree of 65-70% and hydroxymethyl acrylamide are added to the reactor, nitrogen is introduced for protection, heated to 70-80°C, stirred at 500-600r / min for 3-4h, filtered, the filter cake is washed with anhydrous ethanol for 2-3 times, and vacuum dried to obtain a modified binder.
7. The method for preparing a modified silicon oxide battery negative electrode composite material according to claim 6, characterized in that: The reduced product is prepared by the following steps: Add 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, sodium borohydride and deionized water into a reaction kettle in a dosage ratio of 7-9 g:30-40 g:300-400 mL, stir at 70-80° C. and 500-600 r / min for 40-60 min, filter, and wash the filter cake with tetrahydrofuran 2-3 times to obtain a reduced product.
8. The method for preparing a modified silicon oxide battery negative electrode composite material according to claim 6, characterized in that: The dosage ratio of the reducing material, acrylic acid solution, deionized water, stearic acid, sodium sulfite and hydroxymethyl acrylamide is 5-6g:80-90mL:200-300mL:20-30g:80-100mL:80-100mL.
9. A modified silicon oxide battery negative electrode composite material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the modified silicon oxide battery negative electrode composite material according to claim 9 in lithium ion battery negative electrode materials.
Citation Information
Patent Citations
A modified silicon suboxide / carbon nanotube composite anode material and its preparation method
CN112678807B
Lithium battery negative electrode material binder and preparation method thereof
CN116632234A
Silicon monoxide-based negative electrode material and preparation and application thereof
CN119240709A
Silicon-containing composite material
JP2014107013A
System, apparatus and method for monitoring abnormal state of pipe
KR102238436B1